The spectrum of neurologic phenotypes associated with NUS1 pathogenic variants: a comprehensive case series - Brooker, Sarah; Novelli, Maria; Coukos, Robert; Prakash, Neha; Kamel, Walaa A.; Amengual-Gual, Marta; Anheim, Mathieu; Barcia, Giulia; Bardakjian, Tanya; Baur, Franciska; Berweck, Steffen; Bölsterli, Bigna K.; et al. (Annals of neurology, 2025)
Objective A growing body of evidence indicates a strong genetic overlap between developmental and epileptic encephalopathies (DEEs) and movement disorders. De novo loss-of-function variants in NUS1 have been recently identified in DEE cases. Herein, we report a large cohort of cases with pathogenic NUS1 variants and describe their clinical presentation and the details of the associated epilepsy and movement disorders. Methods Cases with NUS1-related disorders were identified through a multicentric international collaboration made possible by the GeneMatcher platform. Clinical data were acquired through retrospective case-note review. Results We identified 41 subjects carrying 38 different pathogenic or likely pathogenic heterozygous NUS1 variants. The majority of cases displayed developmental delays and intellectual disability of variable severity. Epilepsy was present in 68.3% of cases (28/41) with onset typically in early childhood. Strikingly, 87.8% of cases (36/41) presented with movement disorders and for 13 of these cases the movement disorder was not accompanied by epilepsy. The phenomenology of the movement disorders was complex with myoclonus observed in 68.3% of cases (28/41), either in isolation or in combination with dystonia, ataxia, and/or parkinsonism. Seven cases that otherwise did not have prominent movement disorders had mild incoordination and intention tremor, suggestive of cerebellar dysfunction. There was no observed genotype-phenotype correlation, suggesting that other genetic or acquired factors impact the clinical presentation. Interpretation Heterozygous NUS1 pathogenic variants cause a complex neurological disorder, variably featuring developmental and epileptic encephalopathies and a broad spectrum of movement disorders, which represent the major source of neurological disability for most cases. ANN NEUROL 2025;98:561-572
Zuerst veröffentlicht: 01. Juli 2025
Gesehen am 13.11.2025